Designing and evaluating a patient-centred health management system for seniors. (March 2016) - Dhillon, Jaspaljeet Singh; Wünsche, Burkhard; Lutteroth, Christof
Introduction: Telehealth has been widely promoted as a technology to make healthcare more effective and affordable. However, current telehealth systems suffer from vendor lock-in and high cost, and are designed for managing chronic diseases rather than preventing them. Methods: We address shortcomings of existing consumer-level health informatics applications in supporting senior health consumers, and provide designers of such systems with a design framework. We assess the feasibility of patient-centred health management systems (HMSs) that are designed based on the proposed framework. In contrast to traditional telehealth, HMSs are patient centred and aim at enabling health consumers to take control of their own health by providing functionality for health self-management. Quantitative and qualitative methods were adopted in evaluating a prototype HMS. Results: Senior healthcare consumers viewed our HMS prototype positively, and experienced a positive change in their attitude towards their health. We identified requirements and challenges for HMSs. In particular, participants indicated that social networking features must have a clear purpose beyond simple broadcasting of emotions and opinions. Discussion: Our study indicates that seniors are able and motivated to leverage a web-based patient-centred HMS, provided that there are suitable health support applications tailored to their needs. This could be achieved by making it attractive for third party application developers to contribute HMS content.